2008
DOI: 10.1097/01.aoa.0000319831.44975.15
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcome Following Laparoscopic Adjustable Gastric Banding

Abstract: languages. Three months postpartum, women were mailed the Impact of Event Scale (IES) questionnaire, which measures posttraumatic stress symptoms. Demographics and obstetric characteristics were collected from medical records. Statistical analysis was by w 2 test and stress symptoms were analyzed by forward, stepwise logistic regression.The scores showed that 41 (33%) of the women had a low SOC; 68 (56%) had a moderate SOC; and 13 (11%) had a high SOC. There was no significant association between low SOC and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 0 publications
0
38
0
1
Order By: Relevance
“…There was considerable heterogeneity in the studies regarding design, type of surgery, number of cases and control groups. Seven studies (10–16) took BMI into consideration and matched/adjusted for BMI or divided the control group according to BMI. Seven studies (17–23) compared deliveries before and after bariatric surgery, some in the same women and others in different women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was considerable heterogeneity in the studies regarding design, type of surgery, number of cases and control groups. Seven studies (10–16) took BMI into consideration and matched/adjusted for BMI or divided the control group according to BMI. Seven studies (17–23) compared deliveries before and after bariatric surgery, some in the same women and others in different women.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, three studies compared index patients with population‐based or national pregnancy cohorts (24–26). Three studies addressed women with RYGB (11,13,14), four studies women with gastric banding (12,15,16,23), one study addressed women with biliopancreatic diversion (22) and nine included a mixture of women with RYGB and gastric banding (10,17–21,24–26). The number of operated women ranged from 13 to 507 and six studies included fewer than 50 women who had prior bariatric surgery (11,13–15,18,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was suggestive of possible nutritional growth restriction in these pregnancies. Ducarme et al found rates of low birthweight among individuals who had LAGB versus obese comparison group who did not undergo LAGB (7.7% versus 10.65%, P < 0.05).…”
Section: Perinatal Outcomementioning
confidence: 98%
“…Most studies report a reduced incidence of GDM in patients following bariatric surgery . Ducarme et al showed that the incidence of GDM (0% versus 22.1%, P < 0.05) and pre‐eclampsia (0% versus 3.1%, P < 0.05) were lower in the LAGB group than in the obese comparison group. GDM screening in malabsorptive patients, however, requires special considerations.…”
Section: Maternal Outcomementioning
confidence: 99%